Rekayasa Alat Ukur Panjang Gelombang Suara Menggunakan Tabung Resonansi Berbasis Arduino Untuk Pengembangan Praktikum Fisika Dasar - Zuly Budiarso Budiarso; Eddy Nurraharjo; Hersatoto Listiyono (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
The development of digital technology has changed the control system technology from an analog control system to a digital control system. Microcontroller that is often used today is Arduino. With the capabilities that exist in arduino, can be applied to measuring the wavelength of sound. Equipment that is often used in basic physics practicum on sound waves is a resonance tube. The purpose of the resonance tube experiment is to find a condition in which a resonance event occurs which is indicated by an interference event between the sound waves originating from the sound source at the end of the tube and the sound waves reflected by the surface of the water in the tube. By using arduino all these equipment can be replaced. Sound sources can be generated from Arduino whose frequency can be adjusted by using the point of occurrence of the resonance event to be replaced by a sound sensor, for the water level when resonance occurs, a proximity sensor is used whose results are displayed on the LCD screen, while to detect the water level, two light sensors are used. placed at the bottom of the tube and the top of the tube. To adjust the water level in the tube is done by increasing and decreasing the volume of water in the tube.The measurement results using this metode have a higher level of accuracy then manual measurements. Keywords: Arduino, Resonance Tube, Sensor, Wavelength